2017
DOI: 10.1080/20008686.2017.1328963
|View full text |Cite
|
Sign up to set email alerts
|

Emerging microbiota during cold storage and temperature abuse of ready-to-eat salad​

Abstract: Introduction: Ready-to-eat (RTE) leafy vegetables have a natural leaf microbiota that changes during different processing and handling steps from farm to fork. The objectives of this study were (i) to compare the microbiota of RTE baby spinach and mixed-ingredient salad before and after seven days of storage at 8°C or 15°C; (ii) to explore associations between bacterial communities and the foodborne pathogens Listeria monocytogenes, pathogenic Yersinia enterocolitica, and pathogen model organism Escherichia co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
21
2
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 27 publications
(28 citation statements)
references
References 32 publications
4
21
2
1
Order By: Relevance
“…In agreement with previous observations, the phylum Proteobacteria showed the highest total abundance on day 0, followed by phyla Bacteroidetes, Firmicutes, and Actinobacteria [3,6,26,34]. The basal bacterial microbiome of RTE spinach leaves is therefore very similar to that of other minimally processed fruits and vegetables [3,6,27,34,60].…”
Section: Discussionsupporting
confidence: 91%
See 4 more Smart Citations
“…In agreement with previous observations, the phylum Proteobacteria showed the highest total abundance on day 0, followed by phyla Bacteroidetes, Firmicutes, and Actinobacteria [3,6,26,34]. The basal bacterial microbiome of RTE spinach leaves is therefore very similar to that of other minimally processed fruits and vegetables [3,6,27,34,60].…”
Section: Discussionsupporting
confidence: 91%
“…This study investigated the microbiome profiles of RTE spinach leaves washed with different sanitizers (ECAS, PAA) and compared with leaves washed with tap water and not washed at all (control), at three time points over 10 days (day 0, day 5, and day 10). Although a higher proportion of ASVs was found compared to previous studies [26,27], their richness and evenness (alpha diversity) did not significantly differ among the types of sanitizer and the sampling points. We also found that the types of sanitizing washing, apart from a reduced heterogeneity over time, did not significantly influence the community structure of the bacteria (beta diversity).…”
Section: Discussioncontrasting
confidence: 87%
See 3 more Smart Citations